The Practicality of Innovative Blended Learning Through The Meaning (IBLTM) Model Making to Improve Science Literacy - Amijaya, Dody Tisna; Raharjo, Raharjo; Ibrahim, Muslimin; Hawari, Asaduddin Al (Indonesia Emerging Literacy Education, 2024)
Objective: Science literacy is essential for learners because it allows them to understand, analyze, and apply scientific concepts in everyday life and make decisions based on scientific information. This study aims to describe the practicality of the Innovative Blended Learning Model through Interpretation to improve students' science literacy. Method: The research method used was development research. Data collection used observation instruments. Data analysis was implemented using descriptive statistics for practicality tests. Results: The results of the trial showed that the level of practicality of the IBLTM learning model is high, which means that the IBLTM learning model is practical enough to be implemented in biology learning. Novelty: This research presents new findings related to the practicality of the IBLTM model by emphasizing how this model facilitates the process of deep meaning and active involvement of students in learning.